Deconstruction of Moral Messages in the Naruto Shippuden Anime Series: The Pain Attack on Konoha Village Episode Through Roland Barthes' Semiotic Analysis - Nurhidayat, Fahmi; Nurfalah, Faridah (Syntax Corporation Indonesia, 2024)
The Naruto Shippuden Animated Series is one of the best-selling Japanese animated films in Indonesia, the Naruto animated film is widely watched by children both on television and the internet. However, in the Naruto Shippuden animated film there are many violent scenes and adult characters, on that basis the author conducted this study to explore the moral message in the show. Moreover, the Pain Attacking Konoha Village Episode is the most popular episode in the Naruto Shippuden animated series. This series also features various characters with different backgrounds, providing diverse perspectives on morality and action. In every battle depicted, there are layers of meaning that teach values such as courage, sacrifice, and responsibility. The Pain Attacking Konoha Village Episode in particular shows the internal conflict experienced by the main characters, underlining the complexity of moral decisions. The methodology applied in this analysis is a qualitative approach through Roland Barthes' Semiotic Analysis Technique which is based on the identification of signs and markers in Denotative, Connotative and Mythical meanings. This analysis aims to identify how the moral message is conveyed through symbolism and interaction between characters. The findings of this analysis show a number of scenes that implicitly convey moral messages that teach ethics about what is good and right, moral messages of advice, moral messages that show to seek the truth based on facts, moral messages that invite the audience to respect other people's opinions, and moral messages to solve problems with a cool head. It is important to understand that even though there is violence in the show, the values taught serve to motivate the audience to make wise decisions in real life